Dimensi Reward dan Punishment dalam Pendidikan: Perspesktif Hierarki Kebutuhan Maslow - Fatimah, Khusnul; Putra, Valdi Giffari Rahmayati; Viono, Tono; Busri, Hasan (AS-SABIQUN, 2024)
This research explores the impact of rewards and punishments in the educational context, focusing on meeting students' needs based on Abraham Maslow's hierarchy. The aim of this study is to understand how physiological, safety, social, esteem, and self-actualization needs are addressed through the provision of rewards and punishments. This research employs a descriptive qualitative method with a case study approach. The data comprises case book documents on regulations and FGI (Forum Group Interview). Data collection techniques involve document studies conducted to obtain an overview of rewards and punishments and their causative factors. Data analysis techniques use Miles and Huberman's interactive model. The findings of this research indicate that students are motivated in learning through the presence of rewards and punishments. The provision of rewards and punishments is based on students' needs according to Abraham Maslow's basic hierarchy of needs, which is divided into several levels including physiological needs, safety needs, love and belonging needs, esteem needs, and self-actualization needs. Maslow's basic needs are appropriately addressed in the provision of rewards. However, some of these needs are not well met in the findings on punishments. Being wise in giving rewards and punishments becomes a way to ensure that the reinforcement objectives are on target and motivate students.